Sheet Metal 2007 - Micari, Fabrizio; Geiger, Manfred; Duflou, Joost R.; Shirvani, Bez; Fratini, Livan; et al. (Trans Tech Publications, 2007)
Volume is indexed by Thomson Reuters CPCI-S (WoS). Collections of peer-reviewed papers always make excellent sources of knowledge and new ideas for researchers coming from both universities and industry. The present collection in particular provides interdisciplinary and international resources, thus encouraging the close cooperation of material scientists, manufacturing and computer engineers and promoting the diffusion of research results, and technology transfer, in all areas of Sheet Metal Processing and Characterizatio